Enhancing Neorealism: Lessons from India-Russia Defense Cooperation for Iran in the Aftermath of the 2014 Russo-Ukraine Conflict - Ali Emamifar; Bahareh Sazmand; Maziar Mozaffari Falarti (Journal of Eurasian Studies, 2025)
The enduring conflict in Ukraine has resonated globally, significantly impacting international security and diplomatic dynamics, particularly in the arena of military and defense cooperation. This study meticulously examines the aftermath of the conflict, focusing on its implications for the established defense partnership between Russia and India. By scrutinizing pertinent literature and primary sources, this study investigates the reverberations of the Ukraine conflict on Russia-India defense cooperation since 2014. It evaluates how India’s defense procurement strategies have adapted, discerning a deliberate shift towards diversification of defense suppliers beyond Russia. This study also emphasizes that Iran should heed the lessons emanating from the India-Russia defense cooperation outlook. It advocates for Iran to diversify its arms suppliers, heavily invest in its domestic defense industry, and significantly reduce its dependency on Russian weapons. By drawing parallels with India’s post-conflict defense evolution, Iran can chart a trajectory towards bolstering its own defense capabilities autonomously. This necessitates fostering a broader spectrum of international partnerships while concurrently enhancing its indigenous technological prowess. The investigation offers Iran a blueprint inspired by India’s recalibration of defense cooperation following the 2014 Russo-Ukraine conflict, aiming to guide Iran towards a more resilient and self-reliant defense posture.